Pengaruh Ekstrak Daun Sirsak (Annona muricata L) Terhadap Profil Darah dan Kelulushidupan Ikan Lele Sangkuriang (Clarias gariepinus Var. Sangkuriang) yang Diinfeksi Bakteri Aeromonas Hydrophila - Kurniawan, Kurniawan; Prayitno, Slamet Budi; Sarjito, Sarjito; Lusiastuti, Angela Mariana (Journal of Aquaculture Management and Technology, 2013)
The main problem in catfish farms is mass mortality coused by Motile Aeromonas Septicemia (MAS) by Aeromonas hydrophila. Natural ingredients that are currently being developed is soursop leaf. It was because soursop leaf contains acetogenin compounds that wishes compared to other plant parts. An acetogenin compound has the benefit of as an antibacterial. The purpose of this research was to determine the influence and best dose of sourshoup leaf extract in feed to the blood profile and survival rate of catfish infected by A. hydrophila. The treatment in this study were the addition of soursop leaf extract on feed with different dosage and 3 replicates. The treatments were A (0 g/kg diet), B (5 g/kg diet), C (10 g/kg diet), D (15 g/kg diet). The result showed that soursop leaf extract in feed of treatment B on the best dose (5 g/kg diet) was total erythrocytes(1,51 x 106 sel/mm3), total leukocytes (8,00 x 103 sel/mm3), limphocytes (92%), monocyte (8%), neutrophils, phagocytic index (75%), and survival rate (93%). It can be concluded that dose of 5 g/kg diet was the best dosage of soursop leaf extract in the feed that was able to stimulate the immune response of catfish, it was characterized by an increased erythrocytes, total leukocytes, differetial leukocyte (limphocytes and monocyte) of catfish infected by A. hydrophila.